The effect of dexmedetomidine and remifentanil on the postoperative sore throat after thyroidectomy - Kim, Hyuckgoo (Medicine (Baltimore), 2020)
BACKGROUND: Postoperative sore throat (POST) is an important concern in surgical patients undergoing endotracheal intubation. Its prevalence after thyroidectomy is up to 80%. The current study aimed to assess the effect of dexmedetomidine and remifentanil on postoperative sore throat. METHODS: Seventy-four patients who underwent thyroidectomy were randomized to receive either dexmedetomidine (group D) or remifentanil (group R). At anesthesia induction, group D received dexmedetomidine 1 μg/kg over 10 minutes, followed by continuous dexmedetomidine infusion at 0.3 to 0.6 μg/kg/hour during surgery. Group R received remifentanil of 3 to 4 ng/ml during induction, followed by 1.5 to 2.5 ng/ml remifentanil infusion during surgery. POST at rest and swallowing was assessed during the first 24 hours in serial time periods (0–1, 1–6, and 6–24 hours). Hoarseness and postoperative pain score were also assessed. RESULTS: POST incidence at rest (0–1, 1–6, and 6–24 hours) and swallowing (1–6 and 6–24 hours) was lower in group D than in group R. POST severity was significantly lower in group D than in group R during each time period. The incidence of postoperative hoarseness was also lower in group D than in group R at 1 to 6 and 6 to 24 hours. The postoperative pain score was lower in group D than in group R during each time period. CONCLUSION: Intraoperative dexmedetomidine infusion reduced the incidence and severity of POST for 24 hours after thyroidectomy.